Pengetahuan Remaja tentang Perilaku Hidup Bersih dan Sehat (PHBS) sebagai Upaya Pencegahan Covid-19 di Wilayah Kerja Puskesmas Klasaman Kota Sorong - Norma Norma; Rolyn Frisca Djamanmona; Yogik Setia Anggreini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The spread of the Covid-19 virus is so fast, one of the risk factors is People Without Symptoms (OTG) or Carrier. OTG is a person infected with covid-19 but is asymptomatic and can transmit the disease to vulnerable groups. OTG is more experienced by productive groups. The purpose of Community Service activities is to create the activeness and independence of adolescents as a risk group of People Without Symptoms (OTG) is behaving in a clean and healthy life (PHBS) through online media as an effort to prevent covid-19 in the working area of Puskesmas Klasaman Sorong City. PkM method in the form of counseling using an online application, namely Zoom Meeting. The evaluation design uses questionnaires in google form applications to measure knowledge. After being educated, 96.7% of teenagers have good knowledge as much as 93.3%.